2016
DOI: 10.1167/tvst.5.6.3
|View full text |Cite
|
Sign up to set email alerts
|

Release of Moxifloxacin from Contact Lenses Using an In Vitro Eye Model: Impact of Artificial Tear Fluid Composition and Mechanical Rubbing

Abstract: PurposeThe aim of this study was to evaluate and compare the release of moxifloxacin from a variety of daily disposable (DD) contact lenses (CLs) under various conditions using a novel in vitro eye model.MethodsFour commercially available DD conventional hydrogel (CH) CLs (nelfilcon A, omafilcon A, etafilcon A, and ocufilcon B) and three silicone hydrogel (SH) CLs (somofilcon A, narafilcon A, and delefilcon A) were evaluated. These lenses were incubated in moxifloxacin for 24 hours. The release of the drug was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 40 publications
(59 reference statements)
2
15
0
Order By: Relevance
“…These results have been observed in previous studies with moxifloxacin. 38 , 40 There were no significant differences in uptake between CH CLs and SH CLs observed for natamycin and ketotifen fumarate ( P > 0.05), which are also similar to previously published results. 6 , 8 …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These results have been observed in previous studies with moxifloxacin. 38 , 40 There were no significant differences in uptake between CH CLs and SH CLs observed for natamycin and ketotifen fumarate ( P > 0.05), which are also similar to previously published results. 6 , 8 …”
Section: Discussionsupporting
confidence: 91%
“…These drugs have been used to study a range of potential ocular therapies using CL drug delivery. 3 , 6 , 8 , 16 , 38 , 40 A simple extraction approach was developed using methanol as the extraction solvent. The method consists of incubating CLs in methanol for 2 hours to remove the bound drugs, and this was repeated for a total of three cycles.…”
Section: Discussionmentioning
confidence: 99%
“…Under these circumstances, a flow system, such as the OcuFlow system utilised in this study, may be a better model to predict actual conditions found in the eye during normal wear. The release of components from CLs is much slower under a flow system, and is affected by tear volume and flow rate [22,28,32,38]. However, for very hydrophilic compounds such as PEG and HPMC, the release may still be rapid.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in this study Milli-Q water was used to measure the release rates of the compounds instead of an artificial tear fluid. In a previous study evaluating the release of a hydrophilic molecule, moxifloxacin, from CL using the OcuFlow, it was found that the release of the compound was faster in PBS than artificial tear fluid [32]. Similarly, since PEG and HPMC are also hydrophilic, the release of these compounds may also be faster in Milli-Q water than in human tear fluid.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation